A Survey on Green Cloud Computing - Devaraju Hanumanthu (AG Volumes, 2022)
Green cloud computing has been concerned with building cloud computing resources in the way that minimises their environmental effect. Green clouds have the potential to save the significant amount of energy while also lowering operating expenses. Due to the rapid increase in global temperatures, this is now a requirement. A green cloud computing strategy is essential as more enterprises migrate to the Internet of Things (IoT). HPC that is High Performance Computing, corporate, as well as web applications may all be run on the cloud because to its scalability and economics. There has been a rapid increase in the utilisation of big data centres (DC) as even the demand for such data centres grows. This High energy use leads to large operating costs as well as high emissions of greenhouse gases. Cloud computing may have a negative influence on an environment if the right energy solutions are not implemented. Additional heat is released when the use of processing chips increases. As a result of this wasteful heating, the system must be cooled further, which in turn creates additional heat. We must thus find a way to achieve system equilibrium while using less energy. An energy-optimized cloud computing system is possible using a green algorithm. An overview of the green cloud computing is provided, along with information on how it may be implemented. Green cloud applications as well as problems are also discussed in this article.